Edible Origami Paper Innovation to Increase Daily Vegetables Intake - Femyta Anindya Putri; Amelia Putri Nuladhani; Rachel Abelyana (JFCN: Journal of Food, Culinary, and Nutrition, 2025)
Indonesia  has  a  low  level  of  vegetable  consumption,  especially  among  children,  even  though  this type of food is essential for growth and health. According to data from the Basic Health Research (Riskesdas),  around  30.8%  of  toddlers  in  Indonesia  experience  stunted  growth,  and  about  10.2% suffer from malnutrition. This condition increases the risk of child mortality up to 11.6 times higher compared to children with adequate growth and nutrition. Children tend to dislike vegetables due to their taste, texture, and early habits of consuming fast food. The proposed innovation of edible origami  paper  serves  as  a  fun,  educational,  and  nutritious  approach  that  is  both  creative  and contextually  appropriate,  particularly  for  promoting  early  nutrition  awareness.  The  innovative formulation  in  this  folding  paper  utilizes  green  spinach,  purple  cabbage,  and  pumpkin  with  the addition of a binding agent. Proximate analysis was conducted  to determine the main nutritional components, including moisture, ash, protein, fat, carbohydrates, and dietary fiber, and the results were compared with those of fresh vegetables. The analysis showed that the edible origami paper has  a  higher  nutrient  density  than  the  fresh  materials  due  to  the  drying  process,  which  reduces moisture content and increases nutrient concentration. The product  also exhibited good physical properties  such  as  high  folding  strength,  allowing it  to  be  folded  like  conventional  origami.  This innovation  is  expected  to  serve  as  a  creative  and  contextual  approach  to  enhancing  children's nutrition awareness from an early age through an enjoyable, educational, and nutritious medium.